2015
DOI: 10.5944/openpraxis.7.3.206
|View full text |Cite
|
Sign up to set email alerts
|

A case study of scholars’ open and sharing practices

Abstract: Although the open scholarship movement has successfully captured the attention and interest of higher education stakeholders, researchers currently lack an understanding of the degree to which open scholarship is enacted in institutions that lack institutional support for openness. I help fill this gap in the literature by presenting a descriptive case study that illustrates the variety of open and sharing practices enacted by faculty members at a North American university. Open and sharing practices enacted a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 31 publications
1
27
0
1
Order By: Relevance
“…Openness is a sociocultural phenomenon, as is higher education; both are situated in and reflect their specific contexts and cultures (Peter & Deimann, 2013;Siemens & Matheos, 2010). A sociocultural framework is used by Veletsianos (2010Veletsianos ( , 2015 and Kimmons (2012a, 2012b) have found Archer's (2003) social realist theory to be a useful framework. Archer's work identifies three interdependent strata of reality: structure (e.g., institutional systems, policies), culture (e.g., norms, ideas, beliefs), and agency (individual freedom to act).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Openness is a sociocultural phenomenon, as is higher education; both are situated in and reflect their specific contexts and cultures (Peter & Deimann, 2013;Siemens & Matheos, 2010). A sociocultural framework is used by Veletsianos (2010Veletsianos ( , 2015 and Kimmons (2012a, 2012b) have found Archer's (2003) social realist theory to be a useful framework. Archer's work identifies three interdependent strata of reality: structure (e.g., institutional systems, policies), culture (e.g., norms, ideas, beliefs), and agency (individual freedom to act).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Cronin 18 Veletsianos, 2015;Waycott, Sheard, Thompson, & Clerehan, 2013) and power relations and inequality (Czerniewicz, Deacon, Glover, & Walji, 2017;Rowe, Bozalek, & Frantz, 2013;Smyth, Bossu, & Stagg, 2016).…”
Section: Openness and Praxis: Exploring The Use Of Open Educational Pmentioning
confidence: 99%
“…Rolfe (2012) assessed staff awareness and behaviors surrounding OER with a focus on attitude to sharing resources. Veletsianos (2015) …”
Section: Openness and Sharing In The Context Of Distance Educationmentioning
confidence: 99%
“…That being said, copyright remains a subject of debate. It is poorly understood by the wider public (Boldrin & Levine, 2013;Aboyade, 2015), requiring OER organizations to invest in training and in the development of management skills (Chang & Hong, 2014;Caro & Lesko, 2014;Corbett, 2011;Veletsianos, 2015;Hobbs, 2016).…”
Section: Oers and The Lawmentioning
confidence: 99%
“…Siyavula releases its materials under CC BY licenses as a general rule; these are public copyright licenses that allow original works to be freely used, modified and shared (Liu et al, 2014 (Veletsianos, 2015). Even in the higher education sector, it was found that while most academics were aware of copyright licensing, they were unfamiliar with CC licensing (Veletsianos, 2015). In such a context, the literature urges the proactive involvement of educators in clarifying copyright law and fair use in the context of educational practice (Hobbs, 2016;Rolfe, 2012).…”
Section: Open Licensingmentioning
confidence: 99%